Valuation of Network Effects in Software Markets A Complex Networks Approach - Kemper, Andreas; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2010)
The customer base is an important value driver of software companies and a reliable prediction of its development is fundamental for investment decisions. A particularity in software markets is that an individual$1 (Bs purchasing decision is often influenced by other users$1 (Bchoices. Although such customer network effects are evident, their quantitative assessment remain elusive with conventional approaches. This book contributes to closing this gap by developing methods for measuring network effects and their implications for valuation in software markets. Based on the theory of complex networks the book reveals that such diffusion processes highly depend on structural properties of customer networks. Moreover, it depicts that such insights are contributions to improve the quality of valuations in software markets. But the implications of this research also comprise social and political aspects as they can be applied in order to prevent corporate failures in all network effect markets.s
Background and Motivation -- Valuation in Modern Software Markets -- Investment and Company Valuation -- Modern Software Markets -- Reconsideration of Valuation in Software Markets -- Modeling Network Effects in Software Markets -- Network Economics in Software Markets -- Customer-Equity Valuation in Software Markets -- Adoption and Diffusion Models for Software Markets -- Network Effects Valuation Framework For Software Markets -- Reconsideration of Network Effects in Software Markets -- Modeling Customer Networks from a Complex Networks Perspective -- Complex Networks Theory -- Complex Networks Adoption and Diffusion Simulator -- Complex Networks Analysis of Customer Networks -- Complex Networks Framework for Valuation in Software Markets -- Reconsideration of Complex Customer Networks in Software Markets -- Summary, Implications, Limitations, and Outlook -- Summary of Findings -- Implications of Results -- Research Limitations -- Research Outlook -- Executive Summary.
Keywords: Economics; Finance; Banks and banking; Economics/Management Science; Finance /Banking.; Operations Research/Decision Theory; Statistical Physics, Dynamical Systems and Complexity; Quantitative Finance; Financial Economics